Reformas a la ley orgánica de transporte terrestre, tránsito y seguridad vial, la acreditación de puntos a la licencia de conducir de acuerdo a su categoria - Cortez Gómez, Washington Omar (2015)
The subject I proposed to develop entitled "AMENDMENT TO THE ORGANIC LAW OF LAND TRANSPORTATION, TRAFFIC AND ROAD SAFETY, And THE ACCREDITATION POINTS TO DRIVER LICENSE TO YOUR CATEGORY" so I would make the summary. Transport history dates back to 1905, during the government of Gen. Rafael Reyes, when it created the Ministry of Public Works and Transport, in order to meet domestic goods, mining, petroleum, patents and registrations privilege marks, railways, roads, bridges, buildings and national public lands. Among the major works and arrangements in which the Ministry has been a leader, we must remember the first 50 years of the twentieth century, a period which defined the standards for construction and maintenance of highways and roads; it was clean and channeling from different rivers and inspection of shipping companies and registration of vessels. In referring to some concepts we can say in general that any accident is a fact, unplanned, which generates a misfortune or harm. In terms of traffic accident is caused by unforeseen occurrence involving a vehicle or more on roads or highways and causing property damage or personal injury or death of them. Our Traffic Law in its article 34 to establish the concept of traffic violations defined as accidents, said: "There are traffic violations actions or omissions that may be foreseen but not intended by the agent, verified by negligence recklessness, or incompetence, or failure to comply with laws, regulations and traffic ordinances, or lawful orders of the authorities and traffic cop.” In our country there is a flurry of economic, social, commercial, education and work, this leads to the population to massively mobilize land transport for this reason finds its regulation and licensing of movement through the channels enabled the vehicular traffic in order to ensure fitness of drivers in the handling of motor vehicles, including agricultural machinery, and the suitability of them for running with the least possible risk. Transport unions persist in the attempt to reform the new Traffic Law to ensure the scoring system applied to driver's licenses because the licenses are awarded 30 points for the term of its validity, which is five years, each offense, reduces a certain score, depending on the seriousness of this, and the loss of the total score leading to the suspension of licenses. Drivers aim for an increase of 30 points. The Act also establishes the possibility of recovering the lost points, based on half the time of validity of licenses, this recovery can only be for 50% of the points that were lost. The Government aims to speed recovery times through training courses. Our proposal is framed in the axiom that a greater responsibility and risks, corresponds most points; this with the point to establish clear rules to ensure public security over the just right of public transport drivers and trucking to practice their activities with confidence, so that its implementation is reflected in the offer of a service quality and user satisfaction and user, with out prejudice to penalties for violations of the law occurring during the process.